2010
DOI: 10.1007/s00436-010-1863-5
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania mexicana promastigotes secrete a protein tyrosine phosphatase

Abstract: Leishmania mexicana is an intracellular protozoan parasite that infects macrophages and dendritic cells and causes a chronic cutaneous disease. Although many enzymatic activities have been reported in this parasite, the presence of kinases and phosphatases has been poorly studied. These enzymes control the phosphorylation and dephosphorylation of proteins. Specifically, protein tyrosine kinases phosphorylate tyrosine residues and protein tyrosine phosphatases (PTPases) dephosphorylate tyrosine residues. PTPase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 41 publications
(46 reference statements)
1
15
0
Order By: Relevance
“…The surface‐bound acid phosphatases were further divided into three distinct groups according to molecular weight, resistance to sodium tartrate, and substrate affinity (Remaley et al ., ). In addition to those activities described as either intracellular or membrane‐bound, various studies regarding Leishmania described an intense acidic phosphatase activity in the culture medium (Gottlieb & Dwyer, ; Lovelace & Gottlieb, ; Doyle & Dwyer, ; Shakarian & Dwyer, ; Escalona‐Montaño et al ., ). Recent studies have shown that promastigotes and amastigotes of different pathogenic species secrete sAcP via an unconventional mechanism that involves the release of exosome‐like vesicles; however, the possibility that the enzymes are released via a shedding mechanism cannot be ignored (Silverman et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The surface‐bound acid phosphatases were further divided into three distinct groups according to molecular weight, resistance to sodium tartrate, and substrate affinity (Remaley et al ., ). In addition to those activities described as either intracellular or membrane‐bound, various studies regarding Leishmania described an intense acidic phosphatase activity in the culture medium (Gottlieb & Dwyer, ; Lovelace & Gottlieb, ; Doyle & Dwyer, ; Shakarian & Dwyer, ; Escalona‐Montaño et al ., ). Recent studies have shown that promastigotes and amastigotes of different pathogenic species secrete sAcP via an unconventional mechanism that involves the release of exosome‐like vesicles; however, the possibility that the enzymes are released via a shedding mechanism cannot be ignored (Silverman et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Trypanosomatids, such as Trypanosoma and Leishmania , have the ability to hydrolyze organophosphates; this reaction is catalyzed by different protein phosphatases that are classified either as ecto‐/extracytoplasmic and found on the cell surface or as secreted/extracellular isolated from the culture media (Escalona‐Montaño et al ., ; Szoor, ; Cosentino‐Gomes & Meyer‐Fernandes, ; Gomes et al ., ). Both protein phosphorylation and dephosphorylation are important post‐translational modifications for all known eukaryotic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…The data on inhibition of this PTP are incomplete, 200 µM sodium orthovanadate decreases the L. mexicana PTP activity by 64%, 200 µM ammonium molybdate leads to the 66% inhibition, and 50 µM pervanadate resulted in 61% inhibition of the L. mexicana PTP activity. As expected, PTP activity of this enzyme is resistant to 5 nM calyculin and 1 µM okadaic acid [172].…”
Section: Inmentioning
confidence: 81%
“…Leishmania mexicana is capable to secrete PTP of apparent M w 50 kDa [172], though this enzyme is still only poorly characterized. It is secreted by L. mexicana promastigotes, and may be inhibited (at least in part) by the PTP, but not PP inhibitors.…”
Section: Inmentioning
confidence: 99%
“…The occurrence of secreted phosphatase activity was also described in Leishmania , such as L. tropica (Jaffe et al 1990 ), L. mexicana (Menz et al 1991 ) L. donovani (Gottilieb and Dwyer 1982 ) and L. amazonensis (Martiny et al 1996 ). Recently, a study involving the use of two antibodies and specifi c inhibitors showed that L. mexicana secreted phosphotyrosine phosphatases (Escalona-Montaño et al 2010 ).…”
Section: Identifi Cation and Localization Of Membrane-bound Or Secretmentioning
confidence: 99%